Kajian Awal Bulan Kamariah Dalam Kitab Keker Bulan Karya Sayyid Usman - M Basithussyarop, M Basithussyarop; Izzudin, Ahmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
Prolonged polemics regarding the determination of the beginning of the month of kamariah in Indonesia are still occurring, because each group believes it has its own basis and method. Sayyid usman, who is a classical scholar of batavia origin, responded to this problem with his own method of addressing the problem of differences at the beginning of the month. His answer can be found in one of his works, namely in the book of the moon, which discusses the early determination of the kamariah system. This paper focuses on how to determine the beginning of the month in the book of keker bulan. The method used is Library research (library research) with data taken from several sources such as books, journals, which correspond to the title of the study. There are two sources of data, primary data taken from the book of Keker Bulan by Sayyid Usman, while secondary data is data that aims to collect pre-existing information to support primary data. Such as books, journals, articles and other online media. The way the data is collected includes documentation, observation. In the book it is explained that the method of determining the beginning of the moon by sayyid usman uses the naked eye and cannot be less than 7°, so it is concluded that in the script the moon kerk in it refers to the rukyat method.